Multigrid for the Mortar Finite Element for Parabolic Problem (Journal of Computational Mathematics, 2003)
In this paper, a mortar finite element method for parabolic problem is presented. Multigrid method is used for solving the resulting discrete system. It is shown that the multigrid method is optimal, i.e, the convergence rate is independent of the mesh size $L$ and the time step parameter $τ$.